Floral therapy and its representation social for teachers of a university center (Research, Society and Development, 2021)
Objective: To analyze the contents that integrate the social representation of flower essence therapy in its structural analysis for professors at a university center. Methodology: This is a qualitative, descriptive and exploratory study, based on the Theory of Social Representations in its structural approach with 66 university professors from a University Center located in the city of Niterói, Rio de Janeiro. A sociodemographic questionnaire and the technique of free evocation of the inducing term “Floral Therapy” via Google Forms were collected. Inclusion criteria: Voluntary participation by signing the Informed Consent Form (TCLE). Results and Discussion: The group understands flower essence therapy as something from nature, through the use of essences, with alternative potential for treatment. The term nature and essence, present in the possible central nucleus, is reinforced by the other peripheries, as confirmed by the similarity analysis, which shows nature as the element with the strongest connections in the representation. Conclusion: There is a lack of studies on the subject, reinforcing the importance of more publications, training and training of professionals for the use of this practice already legally authorized to be carried out in the Unified Health System.